Interpretation of gender-responsive law in realizing substantive justice for women: A feminist legal theory study of law enforcement in Indonesia - Erlin Faridha; Ni Putu Tya Suindrayani; Rizkina Mewahni (Privietlab, 2026)
Discrimination against women as a vulnerable group is still a structural problem in the Indonesian legal system. Although Article 27 paragraph (1) and Article 28B paragraph (2) of the 1945 Constitution, the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW) Law, the Civil Rights Act, and the Crime of Sexual Violence or Tindak Pidana Kekerasan Seksual (TPKS) Law have been designed in a normatively neutral and gender-responsive manner, substantive protection for women has not been optimally realized in law enforcement practices. This gap is evident in the dominance of formalistic interpretations that apply the law textually without considering the power relations and structural vulnerability of women as victims. This is reflected in the case of Baiq Nuril Maknun who was convicted while defending himself from sexual harassment, as well as various cases of victimization of victims of sexual violence in the evidentiary process in court. This study aims to analyze how gender-responsive legal interpretations can build norms that strengthen women's rights in the Indonesian legal system. The research uses normative legal methods with legislative and conceptual approaches. The analysis was carried out using Feminist Legal Theory, especially liberal feminism and cultural feminism, to examine systemic biases in the application of norms that appear to be textually neutral. The results of the study show that the formalistic approach has not been able to bring substantive justice. Alternatively, gender-responsive legal interpretation offers the principles of substantive equality, contextual reasoning, and anti-subordination to strengthen the protection of women's rights in law enforcement practices in Indonesia.